Evaluasi Penerapan SIMRS Menggunakan Metode HOT-Fit di RSUD dr. Soedirman Kebumen - Abda'u, Prih D; Winarno, Wing Wahyu; Henderi, Henderi (Universitas Nusantara PGRI Kediri, 2018)
Implementation evaluation of Hospital Management Information System (SIMRS) in RSUD Dr. Soedirman Kebumen aims to determine what factors have the greatest successfulness of SIMRS. The variables in this study are system quality, information quality, service quality, system use, user satisfaction, organization structure, facilitating condition, top mamagement support, and net benefits which adapted from the HOT-Fit model by eliminating the organization environment variable and by added top management support and facilitating condition variables. From this study, we can see that the success of SIMRS implementation in RSUD Dr. Soedirman Kebumen determined by aspects of Technology, Human and Organization can be seen that the user satisfaction variable has a positive influence on the net benefits vatiable. Based on the results of t-statistic test by using SMARTPLS software, user satisfaction is the variable that gives the most influence to the net benefits gained from SIMRS.